1991
DOI: 10.1007/bf00169359
|View full text |Cite
|
Sign up to set email alerts
|

The use of Aspergillus niger for the bioconversion of olive mill waste-waters

Abstract: Olive mill waste-water was used for protein production in small-scale experiments, using non-sterilized medium without p H control. A 14 g/l concentration of proteins, 61% chemical oxygen demand removal and a 58% reduction in total phenolic compounds were obtained using an Aspergillus niger strain. The removal of phenolic compounds resulted in a change in the colour of the waste-water from black to brown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 9 publications
3
43
0
2
Order By: Relevance
“…Biodegradation of TOPW coupled with Aspergillus growth induced 64%, 62 % and 48 % of COD, color and phenolic compounds removals respectively after four days of culture.This high removal efficiency could be attributed to both degradation and adsorption of phenolic compounds. In somewhat analogous studies, Hamdi et al [28] reported that the decreased color intensity of the olive mill wastewater was possibly due to both the degradation of some phenolic compounds and the adsorption of the polyphenols and tannins onto the fungal mycelium. Moreover, Andleeb et al [9] showed that the high percentage of the decolorization of dyes by Aspergillus niger is due not only to microbial biotransformation but also to biosorption.…”
Section: Influence Of Optimal Conditions On Topw Decolorizationmentioning
confidence: 94%
“…Biodegradation of TOPW coupled with Aspergillus growth induced 64%, 62 % and 48 % of COD, color and phenolic compounds removals respectively after four days of culture.This high removal efficiency could be attributed to both degradation and adsorption of phenolic compounds. In somewhat analogous studies, Hamdi et al [28] reported that the decreased color intensity of the olive mill wastewater was possibly due to both the degradation of some phenolic compounds and the adsorption of the polyphenols and tannins onto the fungal mycelium. Moreover, Andleeb et al [9] showed that the high percentage of the decolorization of dyes by Aspergillus niger is due not only to microbial biotransformation but also to biosorption.…”
Section: Influence Of Optimal Conditions On Topw Decolorizationmentioning
confidence: 94%
“…Hamdi et al, (1991), Hamdi and Radhouane (1992), Cereti et al, (2004) and Azab (2008) also recorded decrease in COD levels ranging from 35.0 -64.0% using A. niger. However, Kshirsagar (2012) recorded decreased COD levels ranging from 71.0 -85.5% using fungi.…”
Section: Resultsmentioning
confidence: 88%
“…84,85 Aspergillus spp. can also degrade and utilise a wide range of phenolic compounds 86 , including compounds present in olive mill wastewaters [87][88][89] . The ability of Aspergillus spp.…”
Section: Enzyme Production Through Aspergillus Strains On Fruit Wastesmentioning
confidence: 99%